Survey of Rickettsia species in hematophagous arthropods from endemic areas for Japanese spotted fever in China - Tian, Junhua; Liu, Jing; Liu, Jin; Lu, Miao; Chen, Xiaomin; Li, Kun (Frontiers in Cellular and Infection Microbiology, 2024)
Japanese spotted fever (JSF) is caused by Rickettsia japonica, mainly vectored by hard ticks. However, whether R. japonica can be transmitted by other arthropods remains unknown. Moreover, it is of interest to investigate whether other Rickettsia species cause spotted fever in endemic areas. In this study, a survey of Rickettsia species was performed in hematophagous arthropods (mosquitoes, tabanids, and ticks) from endemic areas for JSF in Hubei Province, central China. The results showed that the diversity and prevalence of Rickettsia species in mosquitoes are low, suggesting that mosquitoes may not be the vector of zoonotic Rickettsia species. A novel Rickettsia species showed a high prevalence (16.31%, 23/141) in tabanids and was named "Candidatus Rickettsia tabanidii." It is closely related to Rickettsia from fleas and mosquitoes; however, its pathogenicity in humans needs further investigation. Five Rickettsia species were identified in ticks. Rickettsia japonica, the agent of JSF, was detected only in Haemaphysalis longicornis and Haemaphysalis hystricis, suggesting that they may be the major vectors of R. japonica. Notably, two novel species were identified in H. hystricis ticks, one belonging to the spotted fever group and the other potentially belonging to the ancestral group. The latter one named "Candidatus Rickettsia hubeiensis" may provide valuable insight into the evolutionary history of Rickettsia.